Stingless bees damage broccoli inflorescences when collecting fibers for nest building (Scientia Agricola, 2012)
The stingless bee Trigona spinipes (Fabricius, 1793) (Hymenoptera: Apidae) is an important pollinator for various crops, but constitutes an occasional pest of other plant species since it causes injury to leaves, stems, flowers and fruits while collecting nest materials. The aim of the present study was to determine the damage caused by T. spinipes to a broccoli (Brassica oleracea L. var. italica, Brassicaceae) growing on an organic farm. A significant number of plants (72.5 %) presented damaged inflorescences, while 39% of all of the inflorescences suffered some degree of injury. The activities of T. spinipes caused scarifications on the stems of the inflorescences, and these typically evolved to epidermal cicatrices up to 10 mm wide. In some cases, the lesions were sufficiently deep to cause partial destruction of the vascular tissues, and this lead to thinner (< 5 mm diameter) floral stems that may collapse. To the best of our knowledge, this is the first report concerning the attack of broccoli plants by T. spinipes. The results obtained should serve to highlight the possibility that stingless bees could be responsible for direct and/or indirect damage to vegetable crops, and to stimulate the development of control strategies for these incidental pests.